2022
DOI: 10.1097/ijg.0000000000002093
|View full text |Cite
|
Sign up to set email alerts
|

United States Medicare Reimbursement Trends for Glaucoma Procedures: 2000–2020

Abstract: Purpose: The purpose of this study is to investigate US Medicare reimbursement trends for common glaucoma procedures from 2000 to 2020. Materials and Methods: Current Procedural Terminology codes for Glaucoma procedures in the US centers for Medicare and Medicaid Services database were used to conduct this economic analysis. Reimbursement data from the Physician Fee Schedule look-up tool from the Centers for Medicare and Medicaid Services were compiled for the selected procedures and compensation trends were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…As such, the objective of this study is to investigate Medicare reimbursement trends for commonly performed laryngeal procedures. Inflation-adjusted declines in reimbursement have been found not only in neurosurgery, 4 general surgery, 5 orthopedic surgery, 6 reconstructive plastic surgery, 7 ophthalmology, 21,22 and interventional radiology 23 but also in otolaryngology 9 and its subspecialties. 10,11,24 This study found a 20.3% inflation-adjusted decline in reimbursement of laryngeal procedures.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the objective of this study is to investigate Medicare reimbursement trends for commonly performed laryngeal procedures. Inflation-adjusted declines in reimbursement have been found not only in neurosurgery, 4 general surgery, 5 orthopedic surgery, 6 reconstructive plastic surgery, 7 ophthalmology, 21,22 and interventional radiology 23 but also in otolaryngology 9 and its subspecialties. 10,11,24 This study found a 20.3% inflation-adjusted decline in reimbursement of laryngeal procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Despite well-documented evidence of increased procedural demand year over year across ophthalmology procedures, reimbursement has persistently declined. 9,[13][14][15] Business management groups for ophthalmology practices, ambulatory surgery centers, and hospitals heavily weigh costs, time management, and logistics to maintain sound financial positions. Furthermore, inadequate reimbursements can deter physician surgical utilization by making procedures financially unfeasible, as the investment of time required for patient counseling, surgical procedures, and potential complication management remains unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Medicare reimbursement, largely dictated by CMS, remains an area of concern among ophthalmologists, especially in the context of recent and significant Medicare Physician Fee Schedule Final Rule cuts in 2022 and 2023. Despite well-documented evidence of increased procedural demand year over year across ophthalmology procedures, reimbursement has persistently declined 9,13–15 . Business management groups for ophthalmology practices, ambulatory surgery centers, and hospitals heavily weigh costs, time management, and logistics to maintain sound financial positions.…”
Section: Discussionmentioning
confidence: 99%